Analisis Yuridis Kepastian Hukum Eksekusi Arbitrase Internasional di Indonesia Melalui Studi Kasus Sengketa Himpurna - Sulthan Fadhil Hisyam (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2026)
This study provides a critical appraisal of the legal safeguards governing the enforcement of transnational arbitral awards within the Indonesian jurisdiction, centered on the landmark dispute of Himpurna California Energy Ltd v. PT PLN. Utilizing a normative-juridical research framework with an emphasis on jurisprudential analysis and prevailing statutory structures, this inquiry examines the tension between Indonesia’s international obligations under the 1958 New York Convention and the practicalities of domestic judicial intervention. The findings indicate that the broad interpretative latitude applied to 'public policy' principles by local judicial authorities often functions as an anomaly that obstructs the execution of foreign arbitral mandates. Such unpredictability generates significant juridical risk for global investors and undermines the foundational independence of the arbitral forum. This paper advocates for a fundamental reorientation of the judicial paradigm toward a pro-arbitration stance and underscores the necessity of modernizing national arbitration regulations to bolster Indonesia's economic competitiveness within the global trade ecosystem.